Separable Wave Equation in the Space of Colliding Waves - Mustafa, Halilsoy (Physics Letters A, Elsevier, 1990)
We show that the massive wave equation is separable in two different space—times, both arising from the collision of the cross polarized plane gravitational waves. Exact solutions can be expressed in terms of infinite series.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/0375-9601(90)90756-E) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: space—times; general relativity; gravitational waves; cross polarized plane gravitational waves